Novel magnetically interconnected micro/macroporous structure of monolithic porous carbon adsorbent derived from sodium alginate and wasted black liquor and its adsorption performance - Onsri, Parichart; Dechtrirat, Decha; Nooeaid, Patcharakamon; Eiad-Ua, Apiluck; Amornpitoksuk, Pongsaton; Techasakul, Supanna; Taufiq, Ahmad; Chuenchom, Laemthong (My University, 2021)
The novel and facile preparation of magnetically interconnected micro/macroporous structure of monolithic porous carbon adsorbent (MPCA) were designed and presented herein. The synthesis was achieved via conventional freeze-drying and pyrolysis processes. In this study, sodium alginate and wasted black liquor were employed as starting pre-cursors. Sodium alginate acts as a template of materials, whereas black liquor, the wasted product from the paper industry with plentiful of lignin content and alkaline solution, played an essential role in the reinforcement and activation of porosity for the resulting materials. Moreover, both the precursors were well dissolved in Fe3+ solution, providing a simple addition of a magnetic source in a one-pot synthesis. The interconnected micro/macroporous structures were generated through freeze-drying and, subsequently the pyrolysis process. The obtained cylindrical-shaped monolithic porous carbon adsorbent (MPCA-700) showed high mechanical stability, a high BET specific surface area (902 m2/g). Such aforementioned features were considered suitable to make the synthesized monolith as an adsorbent for the removal of heavy metal ions. The maximum adsorption capacity of MPCA-700 towards Pb2+ ions was 76.34 mg/g at pH 5. The adsorption studies illustrated that adsorption kinetics and isotherm perfectly fitted with the pseudo-second-order kinetics model and Langmuir isotherm, respectively. This work presents a promising pro-tocol to reduce the overall costs in the preparation of renewable adsorbents with good adsorption efficiency and regeneration.
Keywords: Adsorption; Alginate; Black liquor; Hierarchical porous carbon monoliths; Magnetic properties